2017
DOI: 10.7759/cureus.1677
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Eyeball Loss in Four Cities of Colombia

Abstract: Purpose: Describe the socio-demographic characteristics of anophthalmic patients examined at specialized centers of four cities in Colombia to know the different causes of eyeball loss.Method: A transversal retrospective study was done of 511 medical records from the specialized practices of four cities in Colombia. Socio-demographic data of patients who were seen between January 2011 and December 2013 were compiled. SOFA Statistics software v1.4.6 was used for this analysis. An analysis throughout the measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Another study was conducted in Uganda by Davanger, with 207 patients who had undergone previous enucleation surgeries, and the author found similar results to other studies, reporting the traumatic eye removal percentage as 50.7% (8). The most recent study was performed by Moreno-Caviedes et al (9) The authors claimed that 51% of the eyeball loss in Colombia was because of trauma. By contrast, some studies reported that only a small percentage of patients' eye loss arose from trauma (10).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Another study was conducted in Uganda by Davanger, with 207 patients who had undergone previous enucleation surgeries, and the author found similar results to other studies, reporting the traumatic eye removal percentage as 50.7% (8). The most recent study was performed by Moreno-Caviedes et al (9) The authors claimed that 51% of the eyeball loss in Colombia was because of trauma. By contrast, some studies reported that only a small percentage of patients' eye loss arose from trauma (10).…”
Section: Discussionmentioning
confidence: 54%
“…Mcgwin et al (15) claimed that patients aged between 20 and 40 years were more exposed to eye injuries compared with other ages. Cillino et al (16) showed that patients aged under 50 years were more susceptible to eye injuries, whereas Moreno et al (9) reported that eye loss was seen more frequently in Colombia in patients aged over 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…Haile et al [10] studied the causes of eye removal in 282 patients in Ethiopia and found that traumatic globe rupture represented 33% of causes of globe atrophy. Other studies in developing countries documented that nearly 50% of eye loss were due to traumatic eye injuries [11,12]. A higher percentage was reported in a study of eye loss in Turkey by Fazil [13] who noted that 71.9% of included cases were due to eye trauma.…”
Section: Discussionmentioning
confidence: 91%
“…Among these, 351 articles were excluded after title screening and the abstract of the 784 remaining papers was assessed. Finally, 461 publications were excluded following the eligibility criteria and thus, 323 articles that had interpretable data and fulfilled the eligibility criteria were used for data extraction…”
Section: Resultsmentioning
confidence: 99%